2003
DOI: 10.1038/sj.onc.1206425
|View full text |Cite
|
Sign up to set email alerts
|

BCR targets cyclin D2 via Btk and the p85α subunit of PI3-K to induce cell cycle progression in primary mouse B cells

Abstract: The p85a subunit of PI3-K and Btk are two crucial components of the B-cell receptor (BCR) signalling pathway. In the present study, we showed that primary splenic B cells from p85a null and xid (Btk-deficient) mice fail to induce cyclin D2 expression and enter early G1, but not S phase of the cell cycle in response to BCR engagement. Furthermore, these Btk or p85a null B cells displayed increased cell death compared with wild type following BCR engagement. These findings are further confirmed by studies showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 69 publications
4
51
0
Order By: Relevance
“…Previous research has suggested a connection between Btk and FOXO1. In quiescent cells, cyclin D2 expression is blocked by FOXO1 (35), whereas Btk is known to promote cyclin D2 expression in response to BCR cross-linking (27,28,36). We therefore asked whether BCR-mediated downregulation of FOXO1 may be mediated by Btk.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has suggested a connection between Btk and FOXO1. In quiescent cells, cyclin D2 expression is blocked by FOXO1 (35), whereas Btk is known to promote cyclin D2 expression in response to BCR cross-linking (27,28,36). We therefore asked whether BCR-mediated downregulation of FOXO1 may be mediated by Btk.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, calcium-dependent signaling is required for BCRinduced cyclin D expression, activation of CDK4/6 complexes and cell cycle progression [36]. Hence, we examined BCR-induced calcium release following labeling of WT or Bim KO B cells with the cell-permeable calcium-specific fluorophore, Indo-1AM.…”
Section: Anti-igm-mediated Intracellular Calcium Release Is Reduced Imentioning
confidence: 99%
“…To identify why cyclin D2 induction is defective in p85␣ Ϫ/Ϫ splenic B cells, we investigated the activation of NF-B signaling, which is known to regulate genes involved in cell proliferation and survival (61)(62)(63)(64). We found that BCR-induced IKK␤ and I B␣ phosphorylation is impaired in p85␣ Ϫ/Ϫ splenic B cells.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration is the downstream effector of PI-3K, Akt, which has been reported to directly interact with and phosphorylate IKK (65,66). However, the protein kinase C (PKC) inhibitor, Gö6983 blocks BCR-induce I B␣ degradation without affecting Akt phosphorylation, suggesting that PKC may represent an upstream regulator of IKK in splenic B cells (64,67). Of note, inhibition of BCR-mediated capacitative calcium entry and PKC activation blocks cyclin D2 induction (37,64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation